AN ANALYSIS OF SLANG IN NICKI MINAJ’S RAP SONGS “SEEING GREEN” AND “FRACTIONS”: A SOCIOLINGUISTIC STUDY - Marlin Taba Leko; Tri Septa Nurhantoro; Yohanes Angie Kristiawan (JOLALI: Journal of Language and Literature, 2023)
This research analyzes the slang word types used by Nicki Minaj in her songs “Seeing Green” and "Fractions". Thus, it covers two objectives: the types and meanings of the slang words in the song lyrics. This research study uses a descriptive qualitative method. Therefore, the unit of analysis is words or phrases containing slang. The main instrument of the research is the researcher herself by applying the theory slang types by Allan and Burridge (2006) and the theory kinds of meaning by Leech (1974). The findings of this research show that there are 69 data slang words in Nicki Minaj’s songs "Seeing Green" and "Fractions". The analysis findings of the types of slang words show that it can be concluded that the highest data is Imitative with 28 data (40.57%), followed by Fresh and Creative with 18 data (26.08%), and also Flippant with 18 data (26.08%). Besides Flippant, there is Clipping with 4 data (5.79%) and Acronym with 1 data (1.44%). Furthermore, the analysis findings of the meaning types of slang words show that it can be concluded that the highest meaning is Stylistic Meaning with 32 data (46.47%), followed by Reflective Meaning with 19 data 27.53%, Affective Meaning with 14 Data 27.53%, Connotative Meaning with 2 data (2.89%), and followed by Collocative Meaning with 2 data (2.89%). Conceptual meaning and thematic meanings are not found in the songs. Thus, only 5 kinds of meaning are found in Minaj’s songs “Seeing Green” and “Fractions”.